2020
DOI: 10.1002/jclp.23041
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a three‐item version of the Edinburgh Postnatal Depression Scale

Abstract: Objective To develop and validate a brief screening instrument for postpartum depression in resource‐constrained primary care settings. Method Secondary data analysis of a cohort of 305 mothers (Mdnage = 26) attending well‐child check‐ups in six primary care centers in Santiago, Chile, answered the Edinburgh Postnatal Depression Scale (EPDS), the 36‐Item Short Form Health Survey, and the Mini International Neuropsychiatric Interview depression module. A predictive model for postpartum depression was built usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…For example, Bowen et al 43 found a declining trend in the prevalence of depressive symptoms among Canadian women during pregnancy. Martinez et al 48 found a significantly increasing trend of depressive symptoms among women in the USA, while Lau et al 30 found a subtle decreasing–increasing trend among Chinese women. The inconsistent pattern of depressive symptoms may be due to differences in cultural backgrounds 45.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bowen et al 43 found a declining trend in the prevalence of depressive symptoms among Canadian women during pregnancy. Martinez et al 48 found a significantly increasing trend of depressive symptoms among women in the USA, while Lau et al 30 found a subtle decreasing–increasing trend among Chinese women. The inconsistent pattern of depressive symptoms may be due to differences in cultural backgrounds 45.…”
Section: Discussionmentioning
confidence: 99%
“…Most existing studies developing shortened EPDS forms compared the shortened forms to the full EPDS rather than comparing to diagnostic classification for depression. Only three studies validated their shortened forms against major depression classification based on DSM or ICD diagnostic criteria, but these studies included only 63, 19, and 9 major depression cases, 20,22,24 limiting their ability to draw conclusions about the shortened scales' measurement properties. Table 1 presents the items included in each study's shortened form as well as the methods used to create that version.…”
Section: Discussionmentioning
confidence: 99%
“…Shortened forms of the full 10-item EPDS have been developed Table 1. [19][20][21][22][23][24] These include two two-item forms, 19,24 a five-item form, 20 three-and seven-item subscales that measure symptoms of anxiety and depression separately, 21,24 a three-item form, 22 and an eight-item form. 23 None of the development processes for these shortened forms used pre-specified criteria for performance to determine how many items to remove from the full 10-item EPDS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations